امتناع الطبيب عن تقديم المساعدة لمريض في حالة خطر - ملاك لشقر; فاطمة عناني (My University, 2026)
Abstract: In conclusion, this study demonstrates that a physician’s failure to provide assistance to a person in danger constitutes a form of omission punishable by law whenever its objective and personal elements are satisfied. These elements include the existence of a legal and professional duty requiring the physician to intervene, the physician’s awareness of a real danger threatening the patient’s life or physical integrity, and the actual ability to provide assistance without the presence of any lawful justification preventing such intervention. This omission is based on a material element consisting of the physician’s abstention from performing the required medical act and the harmful result arising therefrom, provided that a causal link exists between the omission and the resulting damage. It also requires a mental element founded upon knowledge and intent, whereby the physician consciously and willingly refrains from intervening despite being fully aware of the seriousness of the situation. However, this obligation may cease where the patient expressly refuses treatment through a free and informed decision, after having been adequately informed of the medical and legal consequences of such refusal. In this case, the patient’s refusal constitutes a lawful justification for the physician’s non-intervention. Where all the elements of this omission are established without legal justification, the physician may incur civil liability requiring compensation for the damage suffered by the patient, criminal liability leading to the penalties prescribed by law, and disciplinary liability for breaching the rules and ethical standards of the medical profession. Accordingly, it is clear that the legislator has surrounded the physician’s duty to provide assistance with a comprehensive legal framework aimed at ensuring effective protection of patients and securing the physician’s compliance with his legal, professional, and humanitarian obligations. .............................. ملخص : من خلال هذه الدراسة، يتبين أن امتناع الطبيب عن تقديم المساعدة لشخص في حالة خطر يشكل صورة من صور الامتناع المعاقب عليه قانونا متى توافرت شروطه الموضوعية والشخصية، والمتمثلة في وجود واجب قانوني ومهني يفرض على الطبيب التدخل، وعلمه بقيام خطر حقيقي يهدد حياة المريض أو سالمته الجسدية، وقدرته الفعلية على تقديم المساعدة دون أن يحول دون ذلك سبب مشروع، ويقوم هذا الامتناع على ركن مادي يتجسد في الاحجام عن أداء الواجب الطبي، وما يترتب عنه من نتيجة ضارة تربطها علاقة سببية بسلوك الامتناع، وعلى ركن معنوي قوامه العلم والارادة واتجاه قصد الطبيب إلى عدم التدخل رغم إدراكه لخطورة الوضع. غير أن هذا الالتزام قد ينتفي متى عبر المريض عن رفضه للعلاج تعبير إرادة حرة ومستنيرة، بعد إحاطته علما بالآثار الطبية والقانونية المترتبة على قراره، فيصبح هذا الرفض سببا مشروعا يبرر امتناع الطبيب عن التدخل، وإذا ثبتت أركان هذا الامتناع دون مبرر قانوني، ترتبت في مواجهة الطبيب مسؤولية مدنية تلزمه بجبر الضرر الالحق بالمريض، ومسؤولية جزائية تستوجب توقيع العقوبات المقررة قانونا، فضلا عن مسؤوليته التأديبية عند اخلاله بقواعد المهنة وأصولها الاخالقية. ومن ثم، يتضح أن المشرع أحاط واجب الطبيب في تقديم المساعدة بمنظومة قانونية متكاملة ترمي إلى تكريس حماية فعالة للمريض وضمان احترام الطبيب لالتزاماته القانونية والمهنية والانسانية. ................................... Resume : À travers cette étude, il ressort que le refus du médecin de porter assistance à une personne en situation de danger constitue une forme d’omission pénalement réprimée, dès lors que ses éléments matériels et personnels sont réunis. Cette infraction suppose l’existence d’une obligation légale et professionnelle imposant au médecin d’intervenir, sa connaissance d’un danger réel menaçant la vie ou l’intégrité physique du patient, ainsi que sa capacité effective à lui porter secours sans qu’aucun motif légitime ne l’en empêche. L’élément matériel réside dans l’abstention d’accomplir le devoir médical, ayant entraîné un préjudice en lien de causalité avec cette abstention. Quant à l’élément moral, il repose sur la connaissance du danger, la volonté délibérée de ne pas intervenir et l’intention du médecin de s’abstenir malgré la gravité de la situation. Toutefois, cette obligation peut disparaître lorsque le patient refuse expressément le traitement, à condition que ce refus soit libre, éclairé et exprimé de manière non équivoque, après avoir été pleinement informé des conséquences médicales et juridiques de sa décision. Un tel refus constitue alors un motif légitime justifiant l’abstention du médecin. En revanche, lorsque les éléments constitutifs de cette infraction sont réunis sans justification légale, le médecin engage sa responsabilité civile, l’obligeant à réparer le dommage subi par le patient, ainsi que sa responsabilité pénale, pouvant donner lieu aux sanctions prévues par la loi. Il peut également voir sa responsabilité disciplinaire engagée en cas de violation des règles déontologiques et des principes éthiques de la profession. En définitive, le législateur a instauré un cadre juridique complet régissant l’obligation du médecin de porter assistance, dans le but d’assurer une protection effective du patient et de garantir le respect par le médecin de ses obligations légales, professionnelles et humanitaires.
Keywords: Keywords: Doctor; refusal; crime; failure to provide assistance; patient in danger.; الكلمات المفتاحية: الطبيب، االمتناع، جريمة، عدم تقديم المساعدة، مريض في حالة خطر; Mots-clés : médecin; abstention; infraction; non-assistance; patient en situation de danger.